2021
DOI: 10.1177/17588359211019672
|View full text |Cite
|
Sign up to set email alerts
|

External validity of clinical trials with diverse trastuzumab-based chemotherapy regimens in advanced gastroesophageal adenocarcinoma: data from the AGAMENON-SEOM registry

Abstract: Background: Trastuzumab combined with cisplatin and fluoropyrimidines, either capecitabine or 5-fluorouracile (XP/FP), is the standard first-line treatment for advanced, HER2-positive, gastric cancer patients based on the ToGA trial. Despite the lack of phase III trials, many clinicians administer trastuzumab with alternative regimens. One meta-analysis suggests that substituting cisplatin for oxaliplatin might lead to greater efficacy and less toxicity. Methods: 594 patients with HER2-positive gastroesophagea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 38 publications
1
10
0
Order By: Relevance
“…The main characteristics of the registry, method, and data collection have been reported elsewhere. 6 , 7 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 In brief, the AGAMENON-SEOM is a registry sponsored by SEOM’s Evaluation of Results and Clinical Practice section. It is an observational, noninterventionistic registry of the diagnostic–therapeutic approach according to each participating center’s usual practice.…”
Section: Methodsmentioning
confidence: 99%
“…The main characteristics of the registry, method, and data collection have been reported elsewhere. 6 , 7 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 In brief, the AGAMENON-SEOM is a registry sponsored by SEOM’s Evaluation of Results and Clinical Practice section. It is an observational, noninterventionistic registry of the diagnostic–therapeutic approach according to each participating center’s usual practice.…”
Section: Methodsmentioning
confidence: 99%
“…Our study included only patients with metastatic disease and the median OS and median PFS were better than those in the HERXO study and were similar to those in the other two phase 2 studies, which may suggest that oxaliplatin and fluorouracil work better than oxaliplatin and capecitabine in combination with trastuzumab. Another study supporting this hypothesis was conducted by Jimenez-Fonseca et al [ 22 ], conducted on patients with advanced distal esophageal, GEJ, and gastric adenocarcinomas, in which 158 patients (26.5%) received XELOX+trastuzumab, 86 (14.4%) received FOLFOX+trastuzumab, and 81 (13.6%) received CF+trastuzumab treatment. In the FOLFOX+trastuzumab arm, the median PFS was 9.6 months, and the median OS was 16.5 months; in the CF+trastuzumab arm, the median PFS was 7.8 months, and the median OS was 13.7 months; and in the XELOX+trastuzumab arm, the median PFS was 7.7 months, and the median OS was 13.7 months.…”
Section: Discussionmentioning
confidence: 94%
“…The phase 3 KEYNOTE-811 study will evaluate the efficacy and safety of pembrolizumab in combination with trastuzumab and chemotherapy as first-line therapy in patients with advanced HER2-positive gastric or GEJ adenocarcinoma. In a study comparing FOLFOX+trastuzumab with CF+trastuzumab, grade 3-4 diarrhea was seen in 2.5% of the CF+trastuzumab arm and 9.3% in the FOLFOX+trastuzumab arm; grade 3-4 thrombosis was seen in 8.6% of the CF+trastuzumab arm and 3.5% in the FOLFOX+trastuzumab arm; and grade 3-4 stomatitis was seen in 11% of the CF+trastuzumab arm and 9% in the FOLFOX+trastuzumab arm [ 22 ]. Considering the side effects mentioned in these studies, it can be decided whether the treatment to be added to trastuzumab in HER2-positive patients is FOLFOX or CF.…”
Section: Discussionmentioning
confidence: 99%
“…However, this retrospective French study is vital that the mFOLFOX-T regimen was predominantly used one. In the Agamenon registry, it was reported that the mOS was 16.5 months (95% CI 12.3-24.5), and the mPFS was 9.6 months (95% CI 7.7-12.9) in the FOLFOX-T arm 14 . In this study, it was observed that trastuzumab was administered until progression, unlike in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Only indirect comparisons can be carried out with the TOGA trial and above-mentioned phase II trials. In addition, a few retrospective studies compared different chemotherapeutic agents plus T in HER2-positive GC [14][15][16] .…”
Section: Introductionmentioning
confidence: 99%